Find the length of axes of the conic $9{x^2} + 4{y^2} - 6x + 4y + 1 = 0$
$
A.{\text{ }}\dfrac{1}{2},9 \\
B.{\text{ 3,}}\dfrac{2}{5} \\
C.{\text{ }}1,\dfrac{2}{3} \\
D.{\text{ 3,2}} \\
$
Answer
Verified
509.7k+ views
Hint: In order to solve these types of question, firstly we have to convert the given equation into the equation of an ellipse by simplifying the equation into $\dfrac{{{{\left( {x - a} \right)}^2}}}{{{a^2}}} + \dfrac{{{{\left( {y + b} \right)}^2}}}{{{b^2}}}$ = 0 such that we will get the value of $a$ and $b$ to get the length of major and minor axes and we will get our desired answer.
Complete step-by-step answer:
We have given that,
$9{x^2} + 4{y^2} - 6x + 4y + 1 = 0$
$\Rightarrow$ ${\left( {3x} \right)^2} - 6x + {\left( {2y} \right)^2} + 4y + 1 = 0$
$\Rightarrow$ ${\left( {3x} \right)^2} - 6x + {\left( {2y + 1} \right)^2} = 0$
Adding and subtracting square of $\left( { + 1, - 1} \right)$ on R.H.S, we get
$\Rightarrow$ ${\left( {3x} \right)^2} - 6x + {1^2} - {1^2} + {\left( {2y + 1} \right)^2} = 0$
$\Rightarrow$ ${\left( {3x - 1} \right)^2} - 1 + {\left( {2y + 1} \right)^2} = 0$
$\Rightarrow$ ${\left( {3x - 1} \right)^2} + {\left( {2y + 1} \right)^2} = 1$
$\Rightarrow$ ${\left( {3\left( {x - \dfrac{1}{3}} \right)} \right)^2} + {\left( {2\left( {y + \dfrac{1}{2}} \right)} \right)^2} = 1$
$\Rightarrow$ $9{\left( {x - \dfrac{1}{3}} \right)^2} + 4{\left( {y + \dfrac{1}{2}} \right)^2} = 1$
Converting this into $\dfrac{{{{\left( {x - a} \right)}^2}}}{{{a^2}}} + \dfrac{{{{\left( {y + b} \right)}^2}}}{{{b^2}}} - - - - - - \left( 1 \right)$,
Thus
${\dfrac{{\left( {x - \dfrac{1}{3}} \right)}}{{\dfrac{1}{9}}}^2} + {\dfrac{{\left( {y + \dfrac{1}{2}} \right)}}{{\dfrac{1}{4}}}^2} = 1$
$\Rightarrow$ ${\dfrac{{\left( {x - \dfrac{1}{3}} \right)}}{{{{\left( {\dfrac{1}{3}} \right)}^2}}}^2} + {\dfrac{{\left( {y + \dfrac{1}{2}} \right)}}{{{{\left( {\dfrac{1}{2}} \right)}^2}}}^2} = 1 - - - - - \left( 2 \right)$
Hence this is the equation of ellipse.
Comparing equation (1) and (2), we get
Therefore,$a = \dfrac{1}{3}$ and $b = \dfrac{1}{2}$
Thus, $b > a$
Length of the major axes $ = 2b = 2 \times \dfrac{1}{2} = 1$
Length of minor axes $ = 2a = 2\dfrac{1}{3} = \dfrac{2}{3}$
Note: Whenever we face such a type of question the key concept is that we have to convert the given equation in the form of an ellipse equation such that we will easily find out the value of $a,b$ by comparing the equations .
Complete step-by-step answer:
We have given that,
$9{x^2} + 4{y^2} - 6x + 4y + 1 = 0$
$\Rightarrow$ ${\left( {3x} \right)^2} - 6x + {\left( {2y} \right)^2} + 4y + 1 = 0$
$\Rightarrow$ ${\left( {3x} \right)^2} - 6x + {\left( {2y + 1} \right)^2} = 0$
Adding and subtracting square of $\left( { + 1, - 1} \right)$ on R.H.S, we get
$\Rightarrow$ ${\left( {3x} \right)^2} - 6x + {1^2} - {1^2} + {\left( {2y + 1} \right)^2} = 0$
$\Rightarrow$ ${\left( {3x - 1} \right)^2} - 1 + {\left( {2y + 1} \right)^2} = 0$
$\Rightarrow$ ${\left( {3x - 1} \right)^2} + {\left( {2y + 1} \right)^2} = 1$
$\Rightarrow$ ${\left( {3\left( {x - \dfrac{1}{3}} \right)} \right)^2} + {\left( {2\left( {y + \dfrac{1}{2}} \right)} \right)^2} = 1$
$\Rightarrow$ $9{\left( {x - \dfrac{1}{3}} \right)^2} + 4{\left( {y + \dfrac{1}{2}} \right)^2} = 1$
Converting this into $\dfrac{{{{\left( {x - a} \right)}^2}}}{{{a^2}}} + \dfrac{{{{\left( {y + b} \right)}^2}}}{{{b^2}}} - - - - - - \left( 1 \right)$,
Thus
${\dfrac{{\left( {x - \dfrac{1}{3}} \right)}}{{\dfrac{1}{9}}}^2} + {\dfrac{{\left( {y + \dfrac{1}{2}} \right)}}{{\dfrac{1}{4}}}^2} = 1$
$\Rightarrow$ ${\dfrac{{\left( {x - \dfrac{1}{3}} \right)}}{{{{\left( {\dfrac{1}{3}} \right)}^2}}}^2} + {\dfrac{{\left( {y + \dfrac{1}{2}} \right)}}{{{{\left( {\dfrac{1}{2}} \right)}^2}}}^2} = 1 - - - - - \left( 2 \right)$
Hence this is the equation of ellipse.
Comparing equation (1) and (2), we get
Therefore,$a = \dfrac{1}{3}$ and $b = \dfrac{1}{2}$
Thus, $b > a$
Length of the major axes $ = 2b = 2 \times \dfrac{1}{2} = 1$
Length of minor axes $ = 2a = 2\dfrac{1}{3} = \dfrac{2}{3}$
Note: Whenever we face such a type of question the key concept is that we have to convert the given equation in the form of an ellipse equation such that we will easily find out the value of $a,b$ by comparing the equations .
Recently Updated Pages
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Statement I Reactivity of aluminium decreases when class 11 chemistry CBSE
Trending doubts
10 examples of friction in our daily life
The correct order of melting point of 14th group elements class 11 chemistry CBSE
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE